The Effect of Entrepreneurial Orientation on Sustainability Decisions in SMEs Run By Millennial Generations in Semarang, Indonesia - Dewa, Adenanthera L; Oktavia, Ariana; Rahmasari, Lisda (School of Business, IPB University (SB-IPB), 2023)
This study aims to measure the performance of SMEs run by the millennial generation by investigating the effect of entrepreneurship orientation indicators of innovation, proactivity, and risk orientation on sustainability decisions by using the mediating effect of future orientation. The research was conducted in 160 SMEs run by the millennial generation in Semarang, Indonesia. The sampling was conducted using simple random sampling, while the analysis was performed by examining path analysis using the PLS-SEM technique. The results showed significant influences of innovation, proactivity, and risk orientation on future orientation. The analysis of the mediating role of future orientation showed its capability to strengthen the effects of innovation, proactivity, and risk orientation on sustainability decisions. The findings have implications for allowing millennial generation SMEs to remain competitive in the development of the digital world by making them more future-oriented and to have a better future outlook to mitigate uncertainties in the future by optimizing innovation proactivity and risk orientation. Therefore, the factors critical for the sustainability of millennial SMEs are adjusting strategies that can seize current opportunities and develop digital capabilities and innovation strategies to compete in an increasingly competitive market. Keywords: entrepreneurship orientation, future orientation, sustainability decision, SMEs, millennial generations